Dyskursy, performanse tekstowe i narracje transmedialne polskich piosenek rockowych - Tański, Paweł (Tematy i Konteksty, 2018)
There are a few reasons why a song, in its broad sense, is not the main focus of the present study, but its variety – a particular attention is devoted to the genre of the so-called rock music. Firstly, in my opinion, this work of art currently seems to be the most interesting, resonating, as well as artistically and aesthetically valuable. Secondly, the qualitative and quantitative intensity of the genre is priceless. Thirdly and finally, the influence of this very sort of musical activity on the 20th century is commonly known not only through a powerful impact of various counterculture areas in which rock music found its own reason for existence, but mostly owing to being what it is – a performative artistic output in which different areas of art – music, lyrics, visuals and others – correspond with one another. Awarding the Nobel Prize in Literature in 2016 to Bob Dylan has marked a significant moment in cultural history – the musician gained recognition among the honourable Academy and, by the same token, the song – Dylan’s most commonly used artistic medium has raised cultural awareness, reaching out to a wider public. But did it really have to reach out to listeners? Is it not true that a song has been a soundtrack to our lives being constantly present in them? Maybe the decision which the Academy has made was only a formality – lyrics are very important and it is only up to us what meaning we assign to them. This paper aims to interpret selected lyrics of Polish rock songs, considering them as a significant part of the history of the Polish literature.